(untitled) (Research, Society and Development, 2023)
Objective: to present the historical panorama of health surveillance in the municipality of Belém, Pará under political and governmental aspects at the municipal and state levels. Methodology: this is a narrative review applied through a narrative synthesis. Results: the history of health surveillance in Belém - Pará is marked by a series of governmental actions and health surveillance policies in the imperial (regency to the second reign), republican (sword to oligarchy), interventionist, militaristic and democratic spheres led by all municipal and state politicians of each era. Conclusion: health surveillance in Belém is based on government actions at the municipal and state level with the participation of provincial presidents, auditors, governors, mayors and intendeds of each political epoch in the State of Pará and the Capital to provide the safety of health-related products and services such as medicines, health equipment, public and private establishments that serve the belenenses.